Yerba Mate and Coffee as sources of bioactive compounds supporting oral health and cancer prevention – A review of protective mechanisms - Rybowski, Jakub; Krzyśkowska, Sylwia; Szczupaj, Maciej; Krukowska, Kamila; Redner, Aneta; Smala, Kamila; Buczek, Kacper; Zwierzchlewska, Patrycja; Stanibuła, Dominik (Quality in Sport, 2025)
Yerba mate (Ilex paraguariensis) and coffee (Coffea spp.) are beverages rich in bioactive compounds such as polyphenols, caffeine, and chlorogenic acid, which exhibit antioxidant, anti-inflammatory, and anticancer properties. Their regular consumption may positively influence oral health by modulating the oral microbiome, reducing oxidative stress, and supporting tissue regeneration. Studies indicate that yerba mate may inhibit the proliferation of cancer cells, while coffee, due to its antioxidant content, enhances protective mechanisms against oral cancers. This paper analyzes the beneficial effects of these beverages on oral health and their potential role in cancer prevention.